Acyl-carnitine, C5DC, and C26 as potential biomarkers for diagnosis of autism spectrum disorder in children. (September 2018) - Lv, Qian-Qian; You, Cong; Zou, Xiao-Bing; Deng, Hong-Zhu
Highlights: Blood levels of free carnitine, glutaricyl carnitine, octyl carnitine, twenty four carbonyl carnitine and carnosyl carnitine were significantly lower in Chinese preschool children with autism spectrum disorder (ASD). Our manuscript is the first description about the changes in the acyl-carnitine spectrum in Chinese preschool children with ASD, which indicates potential mitochondrial dysfunction and abnormal fatty acid metabolism in ASD. Importantly, our findings indicate that blood levels of glutaryl carnitine and carnosyl carnitine might be potential biomarkers for diagnosis of ASD. Abstract: Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders that shown a close association with impaired lipid metabolism. The acyl-carnitine spectrum status in Chinese children with ASD has not been reported. In this study, we assessed the levels of blood acyl-carnitines in Chinese children with ASD and examined the relation between acyl-carnitine profiles and the intelligence levels. Blood levels of acyl-carnitines were determined by tandem mass spectrometry in 60 children with ASD and 30 typically developing children. Chinese Wechsler Young Children Scale of Intelligence (C-WYCSI) was used in ASD group. Blood levels of free carnitine, glutaricyl carnitine, octyl carnitine, twenty four carbonyl carnitine and carnosyl carnitine in the ASD group were significantly lower than those in the control group. Glutaryl carnitine and carnosyl carnitine might be potential biomarkers for diagnosis of ASD. The changes in the acyl-carnitine spectrum indicate potential mitochondrial dysfunction and abnormal fatty acid metabolism in preschool ASD children.